Usefulness of FT3 to FT4 Ratio to Predict Mortality in Euthyroid Patients With Prior Cardiovascular Events Undergoing PCI: Five-Year Findings From a Large Single-Center Cohort Study - Yuan, Deshan; Jia, Sida; Zhu, Pei; Zhang, Ce; Liu, Yue; Liu, Ru; Xu, Jingjing; Tang, Xiaofang; Zhao, Xueyan; Gao, Runlin; Yang, Yuejin; Xu, Bo; et al. (Frontiers in Endocrinology, 2021)
Background: In euthyroid patients undergoing percutaneous coronary intervention (PCI), it is still unclear whether free triiodothyronine to free thyroxine (FT3/FT4) ratio can predict the recurrence of cardiovascular events (CVEs). We aim to investigate its association with recurrent long-term adverse events in this population. Methods: 3549 euthyroid patients with prior CVEs history undergoing PCI were consecutively enrolled in our study and subsequently divided into three FT3/FT4 ratio tertiles (T1<2.41, n=1170; 2.41≤T2<2.75, n=1198; T3>2.75, n=1181). The primary endpoint was major adverse cardiovascular and cerebrovascular event (MACCE), a composite of all-cause death, myocardial infarction, stroke and revascularization. The secondary endpoints were all-cause death and cardiac death. Results: The median follow-up time was 5 years. The incidence of all-cause death, cardiac death and MACCE were significantly higher among patients in the lowest FT3/FT4 tertile (P<0.05). After adjustment of confounding factors, decreased FT3/FT4 ratio was independently associated with an increased risk of all-cause death (HR 1.82, 95% CI 1.13-2.93, P=0.014), cardiac death (HR 1.90, 95% CI 1.04-3.46, P=0.036) and MACCE (HR 1.33, 95% CI 1.10-1.60, P=0.003) which was driven mainly by all-cause death. Conclusions: In euthyroid patients with prior cardiovascular events undergoing PCI, FT3/FT4 ratio might be a potential predictor of all-cause and cardiac mortality. Routine assessment of FT3/FT4 ratio might be a simple and effective tool for risk stratification in this specific patient population.